Peningkatan Kualitas Kesehatan Pada Manajemen Konstruksi Saat Pandemi Melalui Sosialisasi Pekerja Proyek - Anisza Ratnasari; Marchelia Gupita Sari; Imaniar Sofia Asharhani (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2020)
The conditions of the COVID-19 outbreak in Indonesia is getting more startling, as experienced by Tangerang Regency. The number of confirmed cases is increasing, even though the wheels of the economy cannot be shut completely. All sectors of the economy carry out strategies in order to remain productive. PT Summarecon Agung, Tbk., A property developer in Tangerang is also perform mitigation. As on other property developers, Summarecon, in implementing construction projects, continues to concentrate workers on the project site at the same time. The density and high interaction between workers is very potential in spreading the virus. The task force for handling Covid-19 PT Summarecon Agung, Tbk was formed to mitigate the spread of the virus in the project. One of its duties is to compile a Health Protocol to Prevent the Spread of Covid-19. This protocol is part of a government policy to achieve construction safety, particularly the health of construction workers. The main protocols in preventing Covid-19, include; establishing a Covid-19 prevention task force, identifying the potential dangers of Covid-19 in the field, providing health facilities in the field and implementing Covid-19 prevention in the field. Pradita University in collaboration with the Summarecon Covid-19 Prevention Task Force to oversee the implementation of health protocols for workers. The series of outreach activities aimed to educate construction workers in an effort to increase health awareness in construction management. The target of this activity is for construction workers to remain productive without neglecting health and safety